Linux Timesaving Techniques for Dummies - Douglas, Susan (Wiley Publishing, 2011)
Formerly known as Red Hat Linux, the Fedora Core distribution is an excellent, no-cost alternative to Windows, Solaris, and other expensive operating systems Red Hat currently controls an estimated seventy percent of the Linux market in the U.S. This book gives experienced and first-time Fedora users sixty concise, step-by-step, timesaving techniques to help them perform tasks with Fedora more efficiently Organized by topic, the techniques are presented in the friendly, easy-to-understand For Dummies style, with a minimum of technical jargon The techniques run the gamut of end-user, system administration, and development tasks, ranging from desktop, file system, RPM, and database tips to Internet server, e-mail server, networking, system monitoring, security, and Linux kernel tricks Covers the latest release of Red Hat's Fedora Core distribution